Returns to education: epistemological problems of quantification and its impact on the formulation of policies - Garcia, Pablo Sebastian (2009)
The development of researches which approach the study of returns to education in order to influence on the making of decisions is frequent. There are conventional procedures to quantify them and to grant scientism to the theoretical affirmations. In most cases individual returns are estimated in terms of incomes. Neither non-pecuniary returns nor externalities are taken into account. Only recently some studies that, in turns, investigate these effects of the education have appeared. Nevertheless, they suffer from substantial problems of quantification. On the other hand, these procedures lead to epistemological debates of greater complexity aimed at achieving a greater empirical meaningfulness of the measurements.